Reading Job intertextually - Dell, Katharine; Kynes, Will (Library of Hebrew bible/Old Testament studies, 2013)
Includes bibliographical references (p. [297]-321)-and indexes
Formerly CIP Uk. - Includes bibliographical references and index
Keywords: Aufsatzsammlung; Bibel / Altes Testament; Intertextualität; Bibel / Ijob